IMPROVING THE PRODUCTION PROCESS IN FOOD UMKM IN DESA MAOS LOR , KECAMATAN MAOS, KABUPATEN CILACAP - Prasetia, Vicky; Supriyono, Supriyono; Rafiq, Arif Ainur; Riyanto, Sugeng Dwi (Jurnal Berdaya Mandiri, 2019)
Maos Lor Village is one of 10 villages in Maos Sub-District, Cilacap Regency. The number of small industries is 18 businesses with 61 workers and home industries with 78 businesses with 66 workers. Small industries and home industries in Maos Lor Village are dominated in the food industry. The income of small industries and home industries in Maos Lor Village is not satisfactory because there are obstacles in some production sectors, one of which is production techniques. Simple technology makes the product less attractive and hygienic. This problem is experienced by the food industry in Maos Lor Village, one of which is vegetable donut business. The vegetable donut business managed by Dusun Lancar residents is less productive because it is constrained by the production process. In this community service some problems in the vegetable donut business in Maos Lor Village were overcome by making improvements to the production machinery, so that it was hoped that vegetable donut production could run smoothly and production could increase.